Reasons for late diagnosis of ankylosing spondylitis in clinical practice - Tatyana Vasilyevna Dubinina; Sh F Erdes (Научно-практическая ревматология, 2010)
Objective: To define reasons for late diagnosis of ankylosing spondylitis (AS) in the outpatient setting. patients aged 18 years or older with the valid diagnosis of AS being first established in their life. Results. The outpatient diagnosis of AS is made 8,1±6,0 years, on average, after the occurrence of the first symptoms of the disease. In 75% of cases, the onset of AS begins with inflammatory back pain. The most common diagnosis made in patients is vertebral osteochondrosis before AS is diagnosed in the outpatient practice. Conclusion. The reasons for late diagnosis of AS are the pattern of the disease at its onset and diagnostic errors.